2022
DOI: 10.1038/s41598-022-25297-w
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of community mental health interventions with patients, relatives, and health professionals during the COVID-19 pandemic: a real-world 9-month follow-up study

Abstract: Since the beginning of the COVID-19 pandemic, the need to implement protocols that respond to the mental health demands of the population has been demonstrated. The PASMICOR programme started in March 2020, involving a total of 210 requests for treatment. Out of those subjects, the intervention was performed in 53 patients with COVID-19 without history of past psychiatric illness, 57 relatives and 60 health professionals, all of them within the area of Salamanca (Spain). Interventions were carried out by profe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 56 publications
0
0
0
Order By: Relevance
“…After 9 months of data collection, an interim study was analysed and showed that fear was a predominant emotion among healthcare workers while sadness and feelings of helplessness were more common among patients. Fear and sadness were also prevalent among family members 17 . The most effective treatments included techniques related to emotional expression and regulation as well as self-care.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After 9 months of data collection, an interim study was analysed and showed that fear was a predominant emotion among healthcare workers while sadness and feelings of helplessness were more common among patients. Fear and sadness were also prevalent among family members 17 . The most effective treatments included techniques related to emotional expression and regulation as well as self-care.…”
Section: Methodsmentioning
confidence: 99%
“…The most effective treatments included techniques related to emotional expression and regulation as well as self-care. Mindfulness was particularly effective among healthcare professionals while grief counselling and providing information about available resources were beneficial for family members 17 . After 18 months of follow-up the program was closed, and no new patient were admitted since October.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation